Effectiveness and Safety Comparison of Clozapine-Haloperidol with Clozapine-Risperidon Regimen in Schizophrenia Inpatients at Prof. Dr. Soerojo Magelang Mental Hospital - Mustikawati, Maria Sri Ayu; Budiman, Bambang Hastha Yoga Legowo; Ikawati, Zullies (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Schizophrenia treatment uses drugs from the antipsychotic group. Antipsychotics combination of clozapine-haloperidol and clozapine-risperidone are widely used in schizophrenia inpatients. Clozapine is often used in combination with haloperidol and risperidone (high-potency antipsychotic) to enhance the blockade of D2 receptors.Objectives: To compare the effectiveness and safety of the clozapine-haloperidol regimen with clozapine-risperidone used by schizophrenia inpatients.Methods: The research design was retrospective cohort observational. Data collection based on medical records of inpatients diagnosed with schizophrenia at Prof. Dr. Soerojo Magelang Mental Hospital in January 2021 - June 2023. The subjects were 142 people (71 people in both groups). Effectiveness was assessed by the difference in pre and post-PANSS-EC scores, as well as clinical improvement through the final PANSS-EC score. Meanwhile, safety was evaluated based on the incidence of drug side effects. The data was then analyzed statistically.Results: The average PANSS-EC score decrease was 10 ± 5.53 in the clozapine-haloperidol group and 11 ± 5.70 in clozapine-risperidone group. Nonetheless, there was no meaningful contrast between them in terms of PANSS-EC difference (p=0.326), or improvement in clinical condition by the final PANSS-EC score (p=0.111). Also, there was no meaningful distinction in the incidence of adverse drug events (p=0.422). However, extrapyramidal syndrome, the most frequent side effect (18 out of 40 cases), had a significant difference with the clozapine-haloperidol group having the most cases (p=0.044).Conclusion: Both regimens are interchangeable in clinical practice. But clozapine-risperidone is better tolerated regarding extrapyramidal side effects.